Displacement and rehabilitation : solutions for the future - Mishra, Nihar Ranjan; Misra, Kamal K., 1954-; Indira Gandhi Rashtriya Manava Sangrahalaya (Bhopal : Indira Gandhi Rashtriya Manav Sangrahalaya ; New Delhi : Gyan Pub. House, 2012)
Papers presented at an international conference held at Rourkela during 13-14 November 2010.
Section 1. Issues on displacement and livelihood -- section 2. Rehabilitation policy and implementation issues and peoples' responses.
Includes bibliographical references and index.
Keywords: Forced migration -- India -- Congresses; Internally displaced persons -- Rehabilitation -- India -- Congresses